QuPath: Open source software for digital pathology image analysis. Issue 1 (December 2017) - Bankhead, Peter; Loughrey, Maurice; Fernández, José; Dombrowski, Yvonne; McArt, Darragh; Dunne, Philip; McQuaid, Stephen; Gray, Ronan; Murray, Liam; Coleman, Helen; James, Jacqueline; Salto-Tellez, Manuel; et al.
Abstract QuPath is new bioimage analysis software designed to meet the growing need for a user-friendly, extensible, open-source solution for digital pathology and whole slide image analysis. In addition to offering a comprehensive panel of tumor identification and high-throughput biomarker evaluation tools, QuPath provides researchers with powerful batch-processing and scripting functionality, and an extensible platform with which to develop and share new algorithms to analyze complex tissue images. Furthermore, QuPath's flexible design makes it suitable for a wide range of additional image analysis applications across biomedical research.